INFEKSI KUSTA PASCA INFEKSI COVID-19 : ANCAMAN PENYAKIT TROPIS TERABAIKAN PASCA PANDEMI BAGI INDONESIA - Simanjuntak, Arya Marganda; Marbun, Patricia Dean Ully; Anggraini, Yuni Eka (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2023)
Background: Leprosy is still a health problem in Indonesia and as the third world largest contributor the number of cases ranging from 8% world’s cases. Leprosy has various challenges in Indonesia, such as negative stigma, public reluctance to seek medical treatment and comply with medication and the pandemic. Pandemic COVID-19 seems to cover up leprosy cases in Indonesia. A Population-based study in Brazil showed that the impact of pandemic as increasing the diagnosis of multibacillary leprosy. Correlation studies COVID-19 and Leprosy is still unknown. No article identified about leprosy and COVID-19 related in Indonesia. Researchers are trying to explore more about leprosy infection and COVID-19 mechanisms that may occur and also probable condition that would happen in Indonesia. Methods: This literature review sourced from Pubmed, Science Direct and Google Scholar according to the inclusion criteria and evaluated and studied. Discussion: Patient would had Lymphopenia after COVID-19. This supports growth of leprosy in the patient’s body as the patient contact with other leprosy patient. The growth will be progressive due to decreased immunity in COVID-19 patients that would persist for a certain period of time. Increasing severity of COVID-19, the greater the susceptibility of the patient to be infected with leprosy. This allows for a sudden spike in leprosy cases after the pandemic. Solution that can be carried out by the government, such as education to eradicate stigma, to serological examination of IgM PGL-1 are needed to find leprosy case as early as possible, especially in patients with sublclinical phase. Finding cases of leprosy as early as possible is needed so that it can be treated before the occurrence of disability in the patient. Conclusion: Infection of COVID-19 would make patient more susceptible for leprosy infection to growth progressively hence increasing case of leprosy after the pandemic if the case is not found as early as possible especially in subclinical phase of Leprosy infection.